(untitled) (Global Journal of Management and Business Research, 2018)
Purpose: The purpose of the study was to investigate how non - performing loans affect the operating profits, and interest income of microfinance institutions. Design/Methodology/Approach: The research concentrated in some selected microfinance institutions within the Kumasi and Accra metropolis where majority is located. The study focused on 6 microfinance institutions in Kumasi and Accra. A total of 140 respondents were administered questionnaires and interviewed out of the total population. These include 20 loan officers, 10 recovery and risk management officers, 10 managers and 100 clients were chosen for the study. The study used purposive sampling and simple random techniques. Primary and secondary data were used for the study. Findings: The study identified the manufacturing sectors have the highest incidence of NPLs. The study discovered a connection between delinquent of recovery and unpaid loans and profitability of the microfinance institutions. A unit change in problem of recovery and outstanding of loans will lead to changes in profitability by 0.685. It was established from the findings of the study that between 2009 and 2014, these selected Microfinance companies recorded 3.60% as the uppermost non-performing loans in 2014 and with the second highest of 2.82% recorded in 2013. The lowest nonperforming loans ratio was recorded in 2009 representing 1.36%. The study also discovered that there is a constant rise in interest income from the loan portfolio from 2009 to 2014. The study further indicated that operating profit was affected as the provision of loans impairment increase. Research Limitations/Implications: In common with others, the study is limited to microfinance in Kumasi and Accra cities of Ghana. The results may differ if replicated in other geographies. Practical Implications: A number of significant implications are drawn from this study, for example, the study will help the managers in microfinance institutions to develop strategies to co